1973
DOI: 10.1042/cs0440163
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Radioimmunoassay for the Measurement of Urinary Tammhorsfall Glycoprotein in the Presence of Sodium Dodecyl Sulphate

Abstract: 1.A specific and quantitative radioimmunoassay was developed for the measurement of low concentrations of human and rabbit Tamm-Horsfall glycoprotein in the presence of other proteins. Antibody-coated tubes were used as a solid phase in the assay and the optimum antibody concentration and duration of antibody coating were established.2. Pure Tam-Horsfall glycoprotein was labelled with '''1 and, because of its apparent susceptibility to radiation damage, was labelled at weekly intervals.3. Sodium dodecyl sulpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The procedure for the determination of THglycoprotein in urine was based on the method described by Grant & Neuberger (1973). These authors used a system involving antibodycoated tubes and iodinated TH-glycoprotein.…”
Section: Selection Of Radioimmunoassay Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for the determination of THglycoprotein in urine was based on the method described by Grant & Neuberger (1973). These authors used a system involving antibodycoated tubes and iodinated TH-glycoprotein.…”
Section: Selection Of Radioimmunoassay Proceduresmentioning
confidence: 99%
“…In the procedure developed for the assay of TH-glycoprotein in urine (Grant & Neuberger, 1973), sodium dodecyl sulphate at 11 mg/l and overnight incubation at 37°C was used to dissociate the TH-glycoprotein. This concentration of sodium dodecyl sulphate was then reduced by dilution to 5 mg/l before assay in order to obtain optimum slope and linearity.…”
Section: Dissociation Of Th-glycoprotein In Serummentioning
confidence: 99%
“…The glycoprotein has since become known as Tamm-Horsfall glycoprotein (THGP). THGP is the most abundant protein in normal urine, about 50 mg of it being excreted daily [4]. Immunofluorescent microscopic analysis and THGP mRNA identification have demonstrated that biosynthesis of the glycoprotein occurs exclusively in cells of the thick ascending Henle loop (TAL) [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, a new ELISA kit became available in 2009 from MD Biosciences GmbH (Zürich, Switzerland). Besides ELISA, radioimmunoassay [52,92,[104][105][106][107][108] , radial immunodiffusion [109,110] and electroimmunoassay [111,112] have also been used in the past. An elegant and highly quantitative immunomethod based on the Luminex platform has been described recently [14] .…”
Section: Biochemical Analysismentioning
confidence: 99%